ANALISIS LEVEL KOGNITIF SOAL UJIAN AKHIR SEMESTER (UAS) GEOGRAFI KELAS XI SEMESTER GASAL SMA NEGERI SE-KOTA PARIAMAN TAHUN PELAJARAN 2019/2020 BERDASARKAN TAKSONOMI BLOOM REVISI ANDERSON - Rahmatul Jannah; Ernawati Ernawati (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to describe the cognitive level of the questions on the geography of SMA Negeri Pariaman as seen from the percentage of questions about Higher Order Thinking Skill (HOTS), Middle Order Thinking Skill (MOTS) and Lower Order Thingking Skill. (LOTS) and describes the teacher's constraints in making HOTS questions and the efforts made to overcome these teacher obstacles. This type of research is descriptive quantitative. The results showed that the cognitive level of the most dominant questions tested was at the Middle Order Thingking Skill (MOTS) level with a percentage of 62% with the question categories at the C2 (understanding) and C3 (applying) levels, while the next dominating questions were at the cognitive level. Lower Order Thingking skill (LOTS) with a percentage of 27% consisting of questions in the C1 category (remembering) and the least tested level is Higher Order Thingking Skill (HOTS) with a percentage of 11% which is in the C4 (analyzing), C5 ( evaluate) and C6 (create). The teacher's constraints in making HOTS questions are constraints in time, constraints originating from students and constraints from the teacher himself. Efforts are made to overcome teacher constraints, namely by reducing the number and lowering the level of questions, deepening the material and LKPD and discussing at the MGMP Forum (Subject Teacher Deliberation).